Demethyleneberberine promotes apoptosis and suppresses TGF‐β/Smads induced EMT in the colon cancer cells HCT‐116. (24th May 2021) - Wang, Zehao; Wang, Lixia; Shi, Boya; Sun, Xiuli; Xie, Yinrong; Yang, Haonan; Zi, Chengting; Wang, Xuanjun; Sheng, Jun
Abstract : Colorectal cancer (CRC) is one of the most common malignant tumours in the world. Recent reports have revealed natural products displayed inhibition on colon cancer potential by suppressing transforming growth factor‐β/Smads induced epidermal‐mesenchymal transition (EMT). In this article, 12 kinds of natural berberine analogues were screened for their effects on the inhibition of the colon cancer cells, the results showed that demethyleneberberine (DM‐BBR) exhibited an interesting and potential effect on inducing the apoptosis of HCT‐116 cells with drug concentrations of 6, 12 and 18 μM. Particularly, DM‐BBR reversed the EMT process by inhibiting the expression of p‐Smad2 and p‐Smad3 in the transforming growth factor‐β/Smads signal pathway, up‐regulated pro‐apoptotic protein cleaved caspase‐9, and blocked cell cycle at the S phase and increasing the expression of cyclin proteins P27 and P21. Taken together, these findings suggested that DM‐BBR could promote apoptosis and suppress TGF‐β/Smads induced EMT in the colon cancer cells HCT‐116.